Pre-service teachers' assessment literacy and its implementation into practice - SÜZÜK, EROL; BEKİROĞLU, FERAL (Routledge, 2014)
This research study was conducted to address pre-service physics teachers' assessment literacy and its implementation into practice. The research was both quantitative and qualitative in nature. For the quantitative aspect of the study, the researchers determined the participants' assessment literacy after their enrolment with the assessment course. Intentions of the qualitative part were to validate the results drawn from the quantitative research and to examine the participants' assessment literacy in the practical realm. Data were collected by using a valid and reliable instrument developed by the first author, a questionnaire and the participants' project assignment including implementation of assessment. According to the quantitative results, the pre-service physics teachers' assessment literacy was quite high. Findings obtained from the qualitative analyses were compatible with the quantitative results. However, the study revealed gaps between assessment literacy in theory and practice. This study suggests that teacher education programmes should highlight theories of assessment as well as types of evaluation, stress validity and reliability of assessment enabling students to engage in both traditional and performance-based assessment methods, and provide opportunities for students to reflect, practice, and revise these methods. © 2014 © 2014 British Educational Research Association.
Keywords: assessment literacy; pre-service teachers; teacher education